Elizabeth Sinkler Coxe's Tales from the Grand Tour, 1890-1910. - LeClercq, Anne Sinkler Whaley (University of South Carolina Press, 2012)
The international adventures of a southern widow turned patron of historical discovery, Elizabeth Sinkler Coxe's Tales from the Grand Tour, 1890-1910 is a travelogue of captivating episodes in exotic lands as experienced by an intrepid American aristocrat and her son at the dawn of the twentieth century. A member of the prominent Sinkler family of Charleston and Philadelphia, Elizabeth "Lizzie" Sinkler married into Philadelphia's wealthy Coxe family in 1870. Widowed just three years later, she dedicated herself to a lifelong pursuit of philanthropy, intellectual endeavor, and extensive travel. Heeding the call of their dauntless adventuresome spirits, Lizzie and her son, Eckley, set sail in 1890 on a series of odysseys that took them from the United States to Cairo, Luxor, Khartoum, Algiers, Istanbul, Naples, Vichy, and Athens. The Coxes not only visited the sites and monuments of ancient civilizations but also participated in digs, funded entire expeditions, and ultimately subsidized the creation of the Coxe Wing of Ancient History at the University of Pennsylvania Museum. A prolific correspondent, Lizzie conscientiously recorded her adventures abroad in lively prose that captures the surreal exhilarations and harsh realities of traversing the known and barely known worlds of Africa and the Middle East. She journeyed through foreign lands with various nieces in tow to expose them to the educational and social benefits of the Grand Tour. Her letters and recollections are complemented by numerous photographs and several original watercolor paintings.